2016
DOI: 10.1111/wvn.12170
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of the Structures and Processes Related to Nurse Supervisory Performance in Long‐Term Care

Abstract: Background: Understanding the structures and processes related to the supervisor performance of regulated nurses (registered nurses [RN] and registered practical nurses [RPN]) is critical in order to discern how administrators of long-term care (LTC) homes can facilitate and better support nurses given their important contribution to nurse assistants' job satisfaction and resident outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
0
20
0
4
Order By: Relevance
“…This review is part of a larger project entitled the ‘Processes, Structures, and Outcomes of Nurse Leadership in LTC Settings’ and the complementary review can be found elsewhere (Chu et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…This review is part of a larger project entitled the ‘Processes, Structures, and Outcomes of Nurse Leadership in LTC Settings’ and the complementary review can be found elsewhere (Chu et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The table consisted of categories for author(s), year of publication, research design, research question/hypothesis, sample size and description, tools and psychometrics, and method of analysis and principle outcomes. Next, the Mixed Methods Assessment Tool was used to review research articles for quality (Table ). Ultimately, 38 articles were chosen for this review, as depicted in Figure , resulting in the development of the three models highlighting workplace civility through a systems perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Flow for study selection MMAT, mixed methods assessment tool used to rate the studies for quality. 27 the three models highlighting workplace civility through a systems perspective.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, nurses comprise almost half of the health workforce (Canadian Institute for Health Information, ). The word “nurse” refers to a profession in which multiple designations exist globally (Canadian Nurses Association [CNA], ; Chu, Ploeg, Wong, Blain, & McGilton, ). Nursing designations include: Registered Nurse (RN), Registered Practical Nurse (RPN), and Licensed Practical Nurses (LPN), amongst others.…”
Section: Introductionmentioning
confidence: 99%